KAIDAH POLA FONOLOGIS TUTURAN BAHASA INGGRIS PASANGAN CROSS MARRIAGE - I Ketut Wardana (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2017)
Abstract This present study investigated any pattern of phonological form and supra segmental distribution on English utterance of cross marriage couples . The research applied qualitative-descriptive design because the data had a deep phenomenological common ground. Language represents a giving meaning and interpretation towards whatever experienced by speakers and explores the opponents’ intentions in natural way. Subject of the study were the cross-marriage couples taken through snowball technique. The focus of the study was the segmental utterances on discourse context which could show any intention interpreted opponents. The data were in the form of utterances of the couples in any kinds of topics collected by recording them. The data was classified into sound elements analyzed by structural phonology and intention delivery analyzed by speech act theory. From the data, it was found that there was some different phonemic transcription, stress contour, pitch, and range of intonation between the speaker from Bali and Speaker from Australia. This was caused by deeply imprinted Balinese sound concepts. The utterances showed the illocutionary force and perlocutionary force. From the stress pattern, it was found that there were some patterns of transition-relevance place and other-speaker turn repetition that indicated to mull over. The last finding was free variants in discourse. The forms of nasalized vowels in non- nasal context showed that the speaker was complaining. Key words: supra segmental, utterance, pragmatics, intention